Hypoxia-related tumor environment correlated with immune infiltration and therapeutic sensitivity in diffuse large B-cell lymphoma - Liu, Chen; Liu, Lin (Frontiers in Genetics, 2022)
Background: Due to the highly heterogeneity of diffuse large B cell lymphoma (DLBCL), traditional chemotherapy treatment ultimately failed in one third of the patients. Big challenge exist in finding how to accurately predict prognosis and provide individualized treatment. Hypoxia though a key factor in the development and progression of DLBCL, its role in DLBCL prognosis has yet to be fully explored. Methods: Data used in the current study was sourced from Gene Expression Omnibus (GEO) database. DLBCL patients were divided according to different hypoxia-related subtypes based on the expressions of hypoxia-related genes (HRGs) relevant to survival. Differentially expressed genes (DEGs) between subtypes were identified by limma package. Using univariate Cox regression and least absolute shrinkage and selection operator (LASSO) analyses, the prognostic signature was established to calculate risk scores. The tumor microenvironment (TME) in low- and high-risk groups were evaluated by single-sample gene set enrichment analysis (ssGSEA) and ESTIMATE. The chemotherapeutic sensitivity in two groups were assessed by IC50 values. Results: DLBCL patients were clustered into two hypoxia-related subtype groupsaccording to different gene survival and expressions associated with increasing oxygen delivery and reducing oxygen consumption, and these two subtype groups were compareds. Based on the differential expression, a risk model was established using univariate cox and LASSO regression analyses, FNDC1, ANTXR1, RARRES2, S100A9 and MT1M. The performance of the risk signature in predicting the prognosis of DLBCL patients was validated in the internal and external datasets, as evidenced by receiver operating characteristic (ROC) curves. In addition, we observed significant difference in tumor microenvironment and chemotherapeutic response between low- and high-risk groups. Conclusion: Our study developed novel hypoxia-related subtypes in DLBCL and identified five prognostic signature for DLBCL patients. Those findings may enrich our understanding of the role of hypoxia in DLBCL and help to improve the treatment of DLBCL patients.